A Case of Colorectal Cancer during Pregnancy: A Brief Review of the Literature - Sepideh Khodaverdi; Ali Kord Valeshabad; Maryam Khodaverdi (Hindawi Limited, 2013)
The incidence of colorectal cancer (CRC) during pregnancy is so rare. Herein we present a case of colorectal cancer that was missed by pregnancy all over the pregnancy period. The patient was a 37-year-old woman (gravid 4, para 2) referred with the complaints of vaginal discharge and suspicious rupture of membrane (ROM). The patient was pale and the initial physical examination revealed dilation of two fingers, effacement about 30%. She underwent emergent cesarean section which showed adhesions surrounding the uterus, the bladder, and the abdominal wall. Forty days postoperatively, the patient presented with abdominal pain in the left upper quadrant (LUQ). Imaging confirmed a mass in LUQ. Partial colectomy of transverse colon (20 cm) was performed. Postoperative histopathologic study revealed a 7 * 6 * 5 cm mass in transverse colon compatible to stage IIa of the Duck class (T3, N0, Mx). Adjuvant chemotherapy was applied and the patient showed improvements during 7 months followup after surgery. Colorectal cancer in pregnancy is associated with diagnostic and therapeutic challenges which mostly lead to late diagnosis in advanced stages and poor prognosis. A targeted program to improve the general population knowledge and the establishment of a national consultant and screening program particularly for women with a planned pregnancy in the high risk group might be beneficial.